QUANTIFICATION AND ANTIBACTERIAL ACTIVITY OF FLAVONOIDS IN COFFEE SAMPLES - Ullah, Riaz; Ahmad, Shabir; Atiq, Aimen; Hussain, Hidayat; Rehman, Najeeb ur; AbdElsalam, Naser M.; Adnan, Muhammad (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Flavonoids are the phenolic substances widely found in fruits, vegetables, grains, bark, roots, stems, flowers, tea and coffee. Methodology: In the current study quantity of flavonoids and antibacterial activities were determined in different coffee samples namely Nescafe classic, Nescafe gold, Nescafe martina, original, creamy and cafe soluvel by using standard methodology available in literature. Results: Nescafe original and gold showed highest content of flavonoid while cafe soluvel showed lowest content of flavonoid. Cafe soluvel, gold and classic showed good antibacterial activities. Conclusion: This study showed that coffee is good source of flavonoids and had excellent antibacterial potential.